1992
DOI: 10.1111/j.2044-8309.1992.tb00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Do people believe behaviours are consistent with attitudes? Towards a cultural psychology of attribution processes

Abstract: In individualistic English-speaking cultures such as Australia, the United Kingdom, or the United States, attitudes and behavioun are often believed to be consistent. By contrast, in the Japanese culture, people may be primarily conceptualized as embedded within social contexts; the belief in consistency between attitudes and behaviour (the ABC belie0 may be less strong and behavioun seen to be less consistent with attitudes. In this paper, we report two studies designed to examine the hypothesis that the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
113
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 16 publications
10
113
0
3
Order By: Relevance
“…This is in line with the finding that Japanese are believed to curtail their expression of opinions relative to Australians (Kashima, Siegal, Tanaka, & Kashima, 1992). The scale included two filler items, making the total of 30 items.…”
Section: Methodsmentioning
confidence: 60%
“…This is in line with the finding that Japanese are believed to curtail their expression of opinions relative to Australians (Kashima, Siegal, Tanaka, & Kashima, 1992). The scale included two filler items, making the total of 30 items.…”
Section: Methodsmentioning
confidence: 60%
“…In contrast, Western thought (both lay and intellectual) has tended to emphasize dispositional explanations (see Miller, 1984;Morris & Peng, 1994, for further discussion of cross-cultural differences in trait vs. contextual orientations). Moreover, other researchers have shown that whereas the Western dispositional orientation emphasizes the elimination of inconsistency, the East Asian interactionist orientation inherently anticipates and tolerates instances of inconsistency (Kashima, Siegel, Tanaka, & Kashima, 1992). East-West differences in dispositionism versus interactionism as well as tolerance versus intolerance of inconsistency raise many exciting questions.…”
Section: Trait Versus Process Orientations and Cultural Differences Imentioning
confidence: 99%
“…Recent cross-cultural work, particularly research comparing members of East Asian and Western cultures, has revealed striking differences in cognition, emotion, and behavior (e.g., Choi, Nisbett, & Norenzayan, 1999;Kashima, Siegal, Tanaka, & Kashima, 1992), as well as fascinating similarities in underlying psychological processes and motives (e.g., attribution for group vs. individual behavior; Menon, Morris, Chiu, & Hong, 1999;and cognitive dissonance;Hoshino-Browne, Zanna, & Spencer, 2005). Stereotyping processes, however, have been the focus of relatively little cross-cultural investigation.…”
mentioning
confidence: 99%